Assessing the Profitability and Long-term Viability of Expansion Plans for the Bambinárium Preschool Network - Hraba, Václav; Kupec, Václav; Ali, Tanweer; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
Bambinárium, a family-owned business, provides preschool services in the highly active Czech early education market. The bachelor's thesis explores how Bambinárium's future growth strategies can sustain profitability and long-term viability. The main objective of the thesis focuses on a comprehensive business analysis of the Bambinárium preschool network and identifying the best expansion strategy which upholds organizational mission—while securing financial stability. The research utilizes a combination of strategic and financial analysis which includes PESTLE, SWOT, Porter’s Five Forces, and VRIO frameworks as well as financial ratio assessment from years 2020-2023. The three designed expansion scenarios (small, medium, and aggressive) undergo thorough analysis with investment appraisal methods (NPV, IRR, ROI, Payback Period) and RAROC risk assessment model—to incorporate risk. The medium expansion scenario demonstrates optimal balance regarding financial profitability while offering feasible project implementation and managed risk tolerance. The thesis concludes with data-based recommendations to guide Bambinárium’s sustainable strategic growth.
Vedoucí práce: Václav Kupec
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses